2017
DOI: 10.1590/s0102-865020170110000004
|View full text |Cite
|
Sign up to set email alerts
|

Nandrolone decanoate appears to increase bone callus formation in young adult rats after a complete femoral fracture

Abstract: Nandrolone decanoate appears to increase bone callus formation in young adult rats after a complete femoral fracture 1 AbstractPurpose: To evaluate the influence of nandrolone decanoate on fracture healing and bone quality in normal rats. Methods: Male rats were assigned to four groups (n=28/group): Control group consisting of animals without any intervention, Nandrolone decanoate (DN) group consisting of animals that received intramuscular injection of nandrolone decanoate, Fracture group consisting of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Flicker et al (15) observed a significant increase in bone mineral content in osteopenic females treated with ND, and considering the potential physiological differences of the species, it is suggested that treatment with ND increases bone mineral content, regardless of sex, in rabbits. Guimarães et al (16) evaluated the influence of ND on bone quality through the evaluation of BMD in male rats after 28 days of treatment and found no significant differences between the treated and control groups. From this, we derive another hypothesis that the beneficial effects of ND may occur later than expected.…”
Section: Discussionmentioning
confidence: 99%
“…Flicker et al (15) observed a significant increase in bone mineral content in osteopenic females treated with ND, and considering the potential physiological differences of the species, it is suggested that treatment with ND increases bone mineral content, regardless of sex, in rabbits. Guimarães et al (16) evaluated the influence of ND on bone quality through the evaluation of BMD in male rats after 28 days of treatment and found no significant differences between the treated and control groups. From this, we derive another hypothesis that the beneficial effects of ND may occur later than expected.…”
Section: Discussionmentioning
confidence: 99%
“…AAS and androgens are generally involved in bone growth and maintenance of bone homeostasis [ 108 ]. Studies show that anabolics do not affect bone quality, but speed up the strengthening process and increase bone callus formation after injury [ 124 ]. Souza et al [ 125 ] described that after administration of nandrolone decanolate, there was no increase in femoral weight or length and there was no difference in relation to the diameter of the epiphysis and the diaphysis.…”
Section: Effect Of Anabolic Steroids On Tissuesmentioning
confidence: 99%
“…It increased the concentration of serum alkaline phosphatase, raised the serum level of phosphorus, and reduced the serum cholesterol level (Komrakova et al 2020). Unlike Ostarine, the commonly used anabolic-androgenic steroid nandrolone decanoate induced femoral fracture in rats after an intake of twenty-seven days, stimulated to a less extent the formation of callus and had no effect on the intact part of the bone (Guimarães et al 2017). On the other hand, the selective androgen receptor modulator S-4 reduced the expected loss of bone substance in an osteoporosis model in rats maintaining bone mineral density and enhancing bone strength (Kearbey et al 2007).…”
Section: Effects On Bonesmentioning
confidence: 99%